Antimicrobial activity of bergamot oil against Trichophyton verrucosum isolated from local cows - EL hafez, Ekbal Abd (Journal of Biochemistry, Microbiology and Biotechnology, 2015)
The fungal infection is zoonotic infectious disease, caused by different species of dermatophytes. In this study, skin scrapings and hair samples were collected from cattle with clinical symptoms of dermatophytosis. The collected samples were directly examined for fungal elements by direct microscopy. Bergamot oil was shown to be a potent antimicrobial agent in vitro against clinically important trichophyton verrucosum. In this study, the activities of bergamot natural essence on trichophyton verrucosum were investigated. The results indicated that the MICs (v/v) of the bergamot oil against the fungi Trichophyton verrucosum was 0.125.